MODEL PEMBELAJARAN VCT TERHADAP ANALISIS BENTUK NORMA SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Oktaviani Putri, Arlinda; Rachmadtullah, Reza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to determine the magnitude of the influence of the VCT model on the analysis of student norm forms in Pancasila education learning. This study uses a quantitative method with a quasi-experimental and Post-test only control group design. Participants in this study were a population involving 5th grade elementary school students. Consisting of 2 classes at SDN KepuhKiriman 1 Waru, namely class 5B (experimental) using the VCT learning model and class 5D (control) using the conventional learning model. The data collection method in this study used test and observation studies. The test used was to see the extent of students' understanding of norm forms. The test contained 10 test questions, and observations were carried out in order to see the extent of the influence of norm forms that existed around. The study shows that the application of the VCT model significantly increases students' understanding of norm values. This finding integrates that the VCT model in elementary schools can be an effective strategy for building students based on norms. Based on the results of the study conducted and processed using SPSS 21, it is known that the t-count is greater than the t-table. Due to the fact that the average score was found in the posttest, the scores of class 5B and 5D were based on the experimental and control groups respectively. From the data analysis, it can be interpreted that there is a positive and significant influence of the VCT Learning Model on the Analysis of Elementary School Students' Norm Forms in Pancasila Education